Кубическая резонансная решетка металлических сфер в магнитодиэлектрической среде - Кулак, Г. К. (ХНУРЕ, 2019)
The solution and analysis of a problem are considered concerning plane wave scattering by a resonance lattice of spherical particles located in magnetodielectric medium.